193k views
1 vote
Use the drop-down menus to complete each equation so the statement about its solution is true. 7 + 2x = 2(x - 1) + 4

User Josema
by
6.0k points

1 Answer

6 votes

Hello, I'll try to make this as easy to understand as possible, anyways, let's begin:

First off, we need to do the multiplication on the right side, like this:

7 + 2x = 2(x - 1) + 4

7 + 2x = 2x - 2 + 4

Now, we need to pass all the x's to one side, and the numbers to the others, like so:

7 + 2x = 2x - 2 + 4

-2x + 2x = - 7 - 2 + 4

Then, we do the addition and subtraction:

-2x + 2x = - 7 - 2 + 4

0x = -5

This means that...

The equation has no solution.

Hope this helped! c:

User Visahan
by
5.6k points